Engines of discovery : a century of particle accelerators - Sessler, A. M. (Andrew Marienhoff) (World Scientific, 2007)
This book for the first time chronicles the development of particle accelerators from the invention of electrostatic accelerators, linear accelerators, and the cyclotron to the colliders of today. It also addresses accelerators employed as sources of x-rays, for medical purposes, and in industrial applications. The book identifies the crucial discoveries in applied physics and engineering that have driven the field and gives the reader insight into the people who made these discoveries as well as the methods they used. Particle accelerators exploit every aspect of today's cutting edge technolo.